Analysis of Total Quality Management Implementation in Higher Education Institutions - Nana Noviada Kwartawaty; Nana Storada Dwi Martadi; Deasy Virka Sari (Indonesian Journal of Business Analytics, 2024)
This article discusses the application of Total Quality Management (TQM) to improve the quality of educational institutions in higher education. To gather information, a library research method was used, involving the exploration of various sources from books, journals, printed materials, and electronic resources. Higher education institutions today are implementing TQM, a system initially used by businesses to enhance the quality of their products and their competitive edge. TQM encompasses four main components: input, process, output, and outcome, with an emphasis on the crucial role of human resources. The primary goal of TQM implementation is to shift from conventional management techniques to contemporary management, where decision-making is fact-based. TQM, therefore, serves as both a replacement for traditional quality assurance methods and as the foundation of quality management. In the context of educational services, client satisfaction forms the basis for fostering client loyalty and continued patronage.